The Effect of Octane Booster and Nitro Race Additives on Engine Performance and Fuel Consumption of 110 CC Motorcycle Engine: An Experimental Approach - Darmulia Darmulia; Obet Ranteallo (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Fuel quality and combustion characteristics are important factors that influence engine performance and fuel efficiency in spark-ignition engines. The use of fuel additives is one method commonly applied to improve combustion quality. Objective: This study evaluated the comparative effects of STP Octane Booster and Nitro Race additives on the engine performance and fuel consumption of a Honda Scoopy 110 cc motorcycle. Methods: A quantitative experimental method was employed using a 2022 Honda Scoopy 110 cc engine. Pertalite (RON 90) and Pertamax Turbo (RON 98) were blended with both additives at five concentration levels (5–25 ml/L). Performance parameters, including torque, power, fuel consumption, specific fuel consumption (SFC), and thermal efficiency, were measured using a chassis dynamometer. Results: Higher additive concentrations consistently increased torque and effective power while reducing fuel consumption and SFC. The combination of STP Octane Booster and Pertamax Turbo yielded the best overall performance among all tested mixtures. Conclusion: STP Octane Booster combined with high-octane fuel positively improved combustion quality and engine performance. These findings suggest that commercially available octane boosters can serve as a cost-effective approach to optimizing fuel efficiency in small motorcycle engines.